Determination of Pu(Ⅵ) in Spent Fuel Solution and 1AF Feed by Absorption Spectrophotometric - LI Ding-ming;ZHANG Yong-shen;LIU Lian-wei;ZHANG Li-hua;LI Hui-bo (He huaxue yu fangshe huaxue, 2021)
Plutonium is the most important product in spent fuel reprocessing. The content of Pu(Ⅵ) in spent fuel solution and 1AF feed affects the recovery of plutonium, so it needs to be measured accurately. In this paper, an analytical method for Pu(Ⅵ) in 1AF was established by absorption spectrometry. The detection limit of the method is 5.8 mg/L, and the recovery are 103% and 96% respectively. Total plutonium content was verified by using the spent fuel solution and 1AF feed with burn-up of 45 000 MWd/tU. The determination results are consistent with those measured by Hybrid K-edge/XRF densitometer method, and the relative deviation is not more than 3%.